Derivatives holdings and systemic risk in the U.S. banking sector - Mayordomo, Sergio; Rodriguez-Moreno, Maria; Peña, Juan Ignacio (Journal of Banking & Finance, 2014)
This paper studies the impact of the banks’ portfolio holdings of financial derivatives on the banks’ individual contribution to systemic risk over and above the effect of variables related to size, interconnectedness, substitutability, and other balance sheet information. Using a sample of 95 U.S. bank holding companies from 2002 to 2011, we compare five measures of the banks’ contribution to systemic risk and find that the new measure proposed in this study, Net Shapley Value, outperforms the others. Using this measure we find that banks’ aggregate holdings of five classes of derivatives do not exhibit a significant effect on the bank’s contribution to systemic risk. On the contrary, the banks’ holdings of certain specific types of derivatives such as foreign exchange and credit derivatives increase the banks contributions to systemic risk whereas holdings of interest rate derivatives decrease it. Nevertheless, the proportion of non-performing loans over total loans and the leverage ratio have much stronger impact on systemic risk than derivatives holdings. Therefore, the derivatives’ impact plays a second fiddle in comparison with traditional banking activities related to the former two items.